A biblical approach to poverty alleviation : a case study of Pinelands Methodist Church, phambili ngeThemba's community building efforts through job creation in Langa township - Muller, Julian C. (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2010.